Stroke in patients with sickle cell disease: clinical and neurological aspects Acidente cerebrovascular em pacientes com anemia falciforme: aspectos clínicos e neurológicos - Carolina Camargo de Oliveira; Sylvia Maria Ciasca; M. Valeriana L. Moura-Ribeiro (Arquivos de Neuro-Psiquiatria)
The aim of this study was to characterize a group of patients (n=8) with sickle cell disease (SCD) and ischemic stroke concerning the clinical, neurological, imaging and progressive aspects. Data were collected from records and completed with an interview of patients and their parents. In this study there were 8 patients with ages ranging from 10 to 23 years old; SCD diagnosis was given between one and two years of age with clinical features of fatigue and anemia. The stroke was ischemic in all individuals and the first cerebrovascular event occurred before 6 years of age; 3 patients had recurrence of stroke despite prophylactic blood transfusion therapy and both cerebral hemispheres were affected in 4 patients. Clinical and neurological current features observed were: acute pain crises, sialorrhea, mouth breathing, motor, and neuropsychological impairments resulting from cortical-subcortical structure lesions. O objetivo deste estudo foi caracterizar um grupo de sujeitos (n=8) com antecedentes de anemia falciforme (AF) e acidente vascular cerebral (AVC) isquêmico, dos pontos de vista clínico, neurológico, radiológico e evolutivo, reavaliados através de exame neurológico e neuropsicológico. A partir de prontuários dos sujeitos com diagnóstico comprovado de AF e AVC, coletamos dados, complementados por entrevista com pacientes e responsáveis. Foram avaliados 8 pacientes; atualmente com idades entre 10 e 23 anos; diagnóstico da AF entre um e dois anos; quadro clínico de fraqueza e anemia. Em todos, o AVC foi isquêmico e o primeiro evento na maioria ocorreu antes dos 6 anos de idade; houve recorrência do AVC em 3, apesar da profilaxia com transfusão sanguínea; ambos os hemisférios afetados em 4; no quadro clínico e neurológico atual constatamos crises dolorosas, sialorréia, respiração oral e importante comprometimento motor e neuropsicológico, resultantes de lesões estruturais cortico-subcorticais.